Importance-performance analysis of tourist perceptions on security services and safety facilities in Nusa Penida, Indonesia - Wahyuni Siska Dwi; Rahman Ari; Suhardono Sapta (BIO Web of Conferences)
This study employs an Importance-Performance Analysis (IPA) to evaluate tourist perceptions of safety measures in Nusa Penida, Indonesia. By assessing the importance and performance of various safety-related indicators such as hazard signs, safety standards, accident first aid, information boards, and CCTV, the study aims to identify strengths and areas for improvement in local safety management. Data were collected from a sample of 60 tourists and analyzed using paired sample t-tests to compare the perceived importance and actual performance of each safety measure. The findings reveal that while essential services like hazard signs and safety standards are both highly valued and well-executed, other areas such as information dissemination via information boards are recognized as underperforming. The study highlights the need for strategic adjustments in resource allocation and emphasizes enhancing communication tools to improve overall tourist safety and satisfaction. The results provide actionable insights for tourism operators and local government agencies to refine safety protocols and improve the effectiveness of safety measures, thereby enhancing the destination’s appeal and ensuring a safer experience for all visitors.